Numerical analysis of the magnetogenesis from early universe phase transitions. Issue 1 (20th January 2021) - Garrison, David
Abstract: We present the results of General Relativistic Magnetohydrodynamic simulations utilizing initial conditions from both the Electroweak and Quantum Chromodynamic (QCD) phase transitions in order to determine if seed magnetic fields may be generated via the Biermann Battery Mechanism of Magnetogenesis. These simulations occur in a simulated early universe between 10 −11 s and 10 3 s after the Big Bang. We find that magnetic fields greater than 10 −20 G may be generated on the Mpc scale. This is believed to be strong enough to generate the large intergalactic magnetic fields seen today. Further work is needed to understand how these fields may have impacted the large‐scale structures we currently observe.